THE EFFECTS OF THE CONTEXTUAL TEACHING AND LEARNING MODEL ON STUDENTS’ CREATIVE THINKING ABILITY BASED ON GENDER - Depi Kurniati; Yanuar Arafat (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
Language was one of the media that played a significant role in creating and producing creative thoughts. However, the process of creative thinking was still rarely trained. The CTL learning model was thought to be effective for improving creative thinking skills. Besides, Creative thinking ability was influenced by gender factors also. This study aimed to examine the effect of the CTL learning model on students’ creative thinking skills, based on gender. This research used quantitative research methods with an Ex-Post facto type. The respondents in this study amounted to 32 people consisting of 25 female students and 7 male students. The data analysis used the simple regression formula with the SPSS 22 program. The results of the simple regression test in this study showed that the CTL learning model affected the thinking ability of female students. The calculated T value was more significant than the T table (3.272> 2.06866) and did not affect male students' creative thinking ability because the T value was smaller than the T table (-1,965 <2,57058). The findings in this study were differences in the results of the regression test between male and female students due to different learning styles and brain structure factors between male and female students caused the role of the teacher in the school will determine the success of the students. This result shows that males and females have different thinking anyway.